Concept of Al-Rahnu and its application at YaPEIM in Shah Alam / Wan Hazirah Ahmad Kamar - Ahmad Kamar, Wan Hazirah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Islamic pawn broking or better known as al-Rahnu has exist long time ago in this world. Al-Rahnu is not a new thing in financial world as it already exist in Rasulullah era. As the time passed, al-Rahnu become unfamiliar in this modern world as the conventional pawn broking took place. However, after consideration made by several institution, the first Islamic pawn broking established by Terengganu Islamic Pawnshop Corporation (MGIT) in 1992. This is as a starting point to the establishment of al-Rahnu service in Malaysia. The concept in al-Rahnu service are used is as an alternative for Muslims society to avoid riba. The alRahnu concept has been modernized so it can adapt with modern world. The objective of this research is to explain the concept and the advantages of al-Rahnu scheme and to discuss the precaution took by Ar-Rahnu YaPEIM in securing the pledge item. Besides that, this research also discuss about the factor of acceptance of al-Rahnu by the community. The method of this research are by doing interview and library research. The area chose by author to done the study is in Shah Alam as it is an urban area and majority of the population are in the middle income group. The branches in Seksyen 17, Shah Alam is randomly selected by the author as the branch are in a strategic location and easy to be found. The result of the study shows that, the concept of al-Rahnu that make it as the advantages of using al-Rahnu is the safe keeping fees charged as the alternative to the interest charged by conventional pawn broking are much lower than the interest charged by conventional pawn broking. Regarding the precaution took by Ar-Rahnu YaPEIM in securing the pledge item, they cover the pledge item with Takaful (Islamic insurance) so that it can cover the loss that might happen besides they implement a condition to the pledger to give the name of their heir so that if anything happen to the pledger, Ar-Rahnu YaPEIM can contact the heir. Concerning about the factor of acceptance by the community on al-Rahnu scheme, study shows that majority of the customer choose Ar-Rahnu YaPEIM because of the low safe keeping fees charged by them. In conclusion, the author give a few recommendation to the other researchers. The recommendation include the research on the factor of acceptance by community on al-Rahnu in a different institution and also, a research on the application of al-Rahnu in a different institution and the author can make the comparison between the institutions chosen.